Desarrollo de un sistema de comunicación y almacenaje de los datos de masas de aceite medidos por los Micro Motions Transmitter en la refinería de aceite de INOLASA - Alpízar-Ramírez, Luis Enrique (Instituto Tecnológico de Costa Rica, 2016)
Automation are processes that have been revolutionized industry, supplanting tasks performed by humans, by mechanisms that made the same work, providing more efficient methods in developing their products. The company, Industrial Oleaginosas Americanas S.A., known as INOLASA, is a company based on the production and marketing of vegetable oils, soy lecithin and food supplies for animal nutrition. Nowadays, the department of oil refinery, of INOLASA industry has a lot of variety of processes and equipment for production. Many processes are controlled manually. One case, is the monitoring the oil production, flowing through ducts where, the reading is visible only in the oil refinery plant, which is located approximately 80 meters from the production offices, where the data is studied. The present project aims to develop a system able to take oils measurements and derivative products, of different equipment used in the plant and finally to be viewed on a computer. For this, it will develop a programming for a microcontroller, which be able to made readings in different equipments of measurement in the plant and communicate with other systems via the company network. Also, it will make a programming for an application, which be able to take data from the local network and store them in a database.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2016.
Keywords: Comunicación serial; Modbus RTU; Comunicación Hart; Base de datos; Red local